Human corpses storage methods used in medical brazilians colleges - Silva, Guilherme Rodrigues da; Cortez, Pedro Olímpio Barros Cavalcante; Lopes, Isabela de Sousa Leal; Teixeira, Bruna de Alcobaça Castelo Branco; Leal, Noelia Maria de Sousa (Revista de Medicina, 2016)
Introduction: Anatomy is the science of body structures and the relations between their structures. One of the oldest methods for the study of anatomy is the use of human cadavers. Given the current difficulty for acquisition of new dead bodies and their importance in the medical education, the conservation of in use cadavers is considered as a crucial point in the teaching of anatomy. Objective: To evaluate the conservation methods of human cadavers used in medical schools in Brazil. Study approach: Descriptive with quantitative approach. Methods: Data collection was carried out by sending an online questionnaire to the email address of those responsible for the Anatomy discipline of 242 Brazilian medical schools. 81 of these institutions answered the research. The data were stored and analyzed by using the programs GoogleForms® and Microsoft Excel®. Results: The data showed that 96% of medical schools makes use of human cadavers in the practical lessons of anatomy. Of that number, 83.33% makes use of formaldehyde and 56.41% of Glycerinating method. The formaldehyde is used for the most of the Brazilians states, except for West Middle of the country. 60,7% of the universities the uses formaldehyde intend to change the method of conservation because of insalubrity of the formaldehyde. Conclusion: The use of human dead bodies in anatomy teaching proved to be of great importance because its use is adopted for a significant part of Brazilian medical schools. The method most widely used in the conservation of cadavers still is formalin fixation, followed by glycerinating.